Cyanine IR-780 for distinguishing 2-amino thiophenols from position isomers. (August 2016) - Sheng, Xiaole; Ye, Zhilan; Liu, Shenghua; He, Wenshan; Ren, Jinghua; Yin, Jun
Abstract: Developing highly selective fluorescent probes for the determination of thiophenol is very significant due to its toxicity influence in biological system. In this work, we firstly found that the commercial available cyanine dye 3H-Indolium, 2-(2-(2-chloro-3-(2-(1, 3-dihydro-3, 3-dimethyl-1-propyl-2H-indol-2-ylidene)ethylidene)-1-cyclohexen-1-yl)ethenyl)-3, 3-dimethyl-1-propyl-, iodide had a remarkable capability of determining the amino-substituted thiophenols. Especially, the 2-amino thiophenol induced a fluorescence change of this cyanine dye with the largest intensity in comparison to the 3- and 4-amino thiophenols, implying Cyanine IR-780 can distinguish 2-amino thiophenols from position isomers. Despite the 2-amino thiophenol quenched the fluorescence of cyanine dye, their complex system further played a role in detecting the glutathione with high selectivity over cysteine and homocysteine. It was worth mentioning that similar selectivity can also be observed in living cells. Graphical abstract: The commercial available cyanine dye (IR-780) had a remarkable capability of determining the amino-substituted thiophenols. Cyanine IR-780 can distinguish 2-amino thiophenols from its position isomers. Moreover, the complex system of 2-amino thiophenol and the fluorescence IR-780 played a role of detecting the glutathione (GSH) with high selectivity over cysteine (Cys) and homocysteine (Hcy). Highlights: Cyanine IR-780 can distinguish 2-amino thiophenols from position isomers. The complex system of 2-amino thiophenol and IR-780 can be used to selectively detect the glutathione. It was successfully applied to the imaging of 2-amino thiophenol and glutathione in living cells.